PROFIT PLANNING ANALYSIS WITH BREAK EVEN POINT APPROACH (BEP) ON BANANA CHIPS BUSINESS “BERKAH JAYA” IN METRO CITY - Kiki Ekasari Khanifah; Nani Septiana (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Planning a good profit will affect the industry's success in obtaining the optimal profit. Profit planning contains measures that will be taken for the industry to reach the magnitude of the desire profit target. Analysis of the Break Even Point is one way or technique use by the leadership of the company to find out on the volume of production or sales volume what is the company operating under the conditions of no benefit nor suffer losses. In General, this analysis also provides information on the Margin of Safety that has uses as an indication and an overview to the management what is the drop in sales can be estimating so that the efforts undertaken do not suffer losses. The purpose of this study is to (1) know the sales volume of the banana chips business berkah jaya to achieve break even point in january until december 2016 (2) knowing the great margin of safety achieved by the banana chips business berkah jaya in january until december 2016 (3) know the minimum amount of sales to be achieved by the banana chips business berkah jaya in order to meet the desire profit target in january until december 2016. Type of this research is descriptive research with quantitative approach. The source of the data used in this research is the primary data and secondary data.The analysis is the analysis of the Break Even Point, the Margin of Safety. The result of showed that based on the calculation of Break Even Point on Banana Chips Business Berkah Jaya on the rupiah is Rp. 8.465.006,51 and based on the units of 995 units in January 2016, amounting to Rp. 11.668.829,29 and 1372 units in February 2016, amounting to Rp. 14.077.171,05 and 1655 units by March 2016, amounting to Rp.12.622.901,73 and 1602 unit in april 2016, amounting to Rp. 9.515.236,749 and 1239 units in may 2016, amounting to Rp. 9.734.292,745 and 1145 units in June 2016, amounting to Rp. 8.297.777,357 and 967 units in July 2016, amounting to Rp. 10.349.909,75 and 1217 units in August 2016, amounting to Rp. 8.830.427,534 and 1034 units in september 2016, amounting to Rp. 11.516.173,31 and 1354 units in October 2016, amounting to Rp. 14.669.596,67 and 1725 units in november 2016, and Rp. 15.031.310,22 and 1965 units in December 2016. Keyword : Profit Planning, Break Even Point, Margin of Safety.